Hyperspectral imaging and characterization of allergic contact dermatitis in the short‐wave infrared. Issue 9 (18th June 2020) - Du, Tommy; Mishra, Deependra K.; Shmuylovich, Leonid; Yu, Andy; Hurbon, Helena; Wang, Steven T.; Berezin, Mikhail Y.
Abstract: Short‐wave infrared hyperspectral imaging is applied to diagnose and monitor a case of allergic contact dermatitis (ACD) due to poison ivy exposure in one subject. This approach directly demonstrates increased tissue fluid content in ACD lesional skin with a spectral signature that matches the spectral signature of intradermally injected normal saline. The best contrast between the affected and unaffected skin is achieved through a selection of specific wavelengths at 1070, 1340 and 1605 nm and combining them in a pseudo‐red‐green‐blue color space. An image derived from these wavelengths normalized to unaffected skin defines a "tissue fluid index" that may aid in the quantitative diagnosis and monitoring of ACD. Further clinical testing of this promising approach towards disease detection and monitoring with tissue fluid content quantification is warranted. Abstract : Hyperspectral imaging in the invisible to human eyes shortwave infrared (SWIR) spectral range was applied to enhance the contrast and reveal underlying mechanistic clues behind ACD—a clinically relevant skin condition caused by a variety of common allergens. Color images generated from the identified three specific wavelengths in SWIR were used to establish a tissue fluid index as a quantitative, proof of concept measure of the skin problem.